âSosiologi Informasi Pengobatan Tradisional Religiusâ Kajian di Masyarakat Perdesaan Jawa Barat - Rahman, Mohammad Taufiq; Sulthonie, Ahmad Agus; Solihin, Solihin (LP2M IAIN Palangka Raya, 2018)
The process of information sociology is an activity of how people create, acquire, change, and store information related to traditional healing practices. This study is aimed at finding information about the treatment on religious traditional healing in certain social groups, in this case the people of West Java. This research is also aimed at examining in how people respond the public policy on traditional healing. The method used in the study is qualitative method using data collecting techniques through observation, interview, documentation and literature studies. The study revealsÂ Â that there were local information sociology activities in the West Java community. This is characterized by traditional activities, patients, government regulations and sociological information activities leading to care of traditional healing services. Although it is still traditional, sociological information activities can help people to preserve the culture of traditional healing. This research can contribute to the development of communication and information sciences as well as guidelines to search the local culture of traditional healing.